Numerical simulation on performances of plane and curved winglet type vortex generator pairs with punched holes. (November 2016) - Lu, Gaofeng; Zhou, Guobing
Highlights: Curved vortex generators show better thermo-hydraulic performance than plane ones. Punching holes at the surface of VGs can improve the thermo-hydraulic performance. The heat transfer mechanism of VGs with punched holes is clarified by FSP theory. The optimal ratio of hole area to VG area is 0.06 considering overall performance. Punching holes at lower position and close to leading edge gives better performance. Abstract: Thermal and flow characteristics of plane and curved vortex generators (VGs) with and without punched holes on their surfaces are investigated and the corresponding mechanism of heat transfer is analyzed. 3-D numerical simulations are carried out in a channel flow fitted with a pair of VGs to the bottom wall with Re varying from 700 to 26, 500. The heat transfer enhancement and pressure loss are examined using the dimensionless parameters Nu m / Nu m0, f / f 0 and R = ( Nu m / Nu m0 )/( f / f 0 ). The results show that VGs with punched holes present higher heat transfer enhancement and lower flow resistance than those without holes and the value of R is increased by 9.8–15% under the present conditions. Further parametric study suggests that the ratio of hole area to the VG area should be optimized to achieve better heat transfer enhancement. And punching holes at a lower position and close to the leading edge gives better thermal–hydraulic performance. The mechanism of heat transfer enhancement is explored with the help of field synergy principle (FSP) and secondary flow theory. Take the delta winglet pair (DWP) for example, the area – average synergy angle θ s between velocity vector and temperature gradient of the cross section along flow direction first increases sharply to a peak of 85.7° before the VGs, After that, it declines dramatically to 81.8° and then climbs back and stabilizes around 89°. Correspondingly, the Nu m / Nu m0 shows the opposite trend to θ s . It is confirmed that the maximum value of heat transfer augmentation is achieved at the minimum synergy angle, which indicates that the mechanism of heat transfer enhancement can be well explained by FSP.